2017
DOI: 10.1038/srep44331
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented large inverted repeats at the replication terminus of circular bacterial chromosomes suggest a novel mode of chromosome rescue

Abstract: The first Lactobacillus delbrueckii ssp. bulgaricus genome sequence revealed the presence of a very large inverted repeat (IR), a DNA sequence arrangement which thus far seemed inconceivable in a non-manipulated circular bacterial chromosome, at the replication terminus. This intriguing observation prompted us to investigate if similar IRs could be found in other bacteria. IRs with sizes varying from 38 to 76 kbp were found at the replication terminus of all 5 L. delbrueckii ssp. bulgaricus chromosomes analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Evidence for fold-back inversions has been found in the genomes of viruses (28), prokaryotes (29), is associated with genetic disease (22,30,31) and a variety of cancers (32-34) Moreover, fold-back inversions observed in human cancer cells having escaped telomere-driven crisis occur independently of DSB repair (35,36), consistent with our findings. Thus, we anticipate that this study will contribute to the understanding of rapid genome evolution, pathogenesis and tumorigenesis.…”
supporting
confidence: 90%
“…Evidence for fold-back inversions has been found in the genomes of viruses (28), prokaryotes (29), is associated with genetic disease (22,30,31) and a variety of cancers (32-34) Moreover, fold-back inversions observed in human cancer cells having escaped telomere-driven crisis occur independently of DSB repair (35,36), consistent with our findings. Thus, we anticipate that this study will contribute to the understanding of rapid genome evolution, pathogenesis and tumorigenesis.…”
supporting
confidence: 90%
“…The natural occurrence of long inverted repeats close to the replication termination site in bacteria with circular chromosomes appears to be rare, based on a recent analysis of 1373 sequenced genomes [ 40 ]. According to the authors, among bacteria that had not been manipulated artificially, this property was found only in the branch of Lactobacillus delbrueckii designated subsp .…”
Section: Discussionmentioning
confidence: 99%
“…The most intriguing features of this strain are the large size of the repeats (553 kb, versus only 38 kb in L. delbrueckii subsp . bulgaricus [ 40 ]) for each copy of the duplicated region, and the loss of its natural replication termination machinery, for which the dif and xerCD genes were probably the most important elements [ 32 ]. The aforementioned analysis of 1373 genomes [ 40 ] dealt only with deposited assemblies and not with raw sequencing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transposable elements often contain genes of interest encoding traits such as antibiotic resistance and bacteriocin production (Klaenhammer, 1993;Toomey et al, 2009). In some cases, critical processes such as genome replication are also intrinsically linked to the presence of inverted repeats (El Kafsi et al, 2017) and structure variants of large genomic transfers between species often harbor crucial mechanisms (Kant et al, 2011). Progress in this area will have a significant impact on determining some of the poorly understood traits associated with LAB (Teusink and Molenaar, 2017).…”
Section: The Impact Of Genomics On Lactic Acid Bacteriamentioning
confidence: 99%